Hubungan Status Sosial Ekonomi dengan Konsep Diri Siswa - Nurhasnah Nurhasnah; Joni Indra Wandi; Randi Saputra (Ikhtisar: Jurnal Pengetahuan Islam, 2022)
The purpose of the study was to describe: (1) socioeconomic status, (2) self-concept, (3) the relationship between socioeconomic status and students' self-concept. The method used in this research is descriptive quantitative correlation type, with a population of research 332 students of SMAN 1 Rao Pasaman. A sample of 182 students, selected by Proportional Stratified Random Sampling using a Likert scale model instrument. The results showed that: (1) socio-economic status was seen from the education level of the parents with a percentage of 45.58% with the category of basic education level, namely: did not pass SD, SD, and SLTP, socio-economic status was seen from the type of work of parents with percentage of 62.4% with semi-skilled category, socioeconomic status seen from the total income of parents with a percentage of 45.3% in the category below one million rupiah, (2) students' self-concept is in the positive category with a percentage of 68.88% from ideal, (3) there is a significant relationship that positive relationship between socioeconomic status and students' self-concept, the contribution of socioeconomic status to self-concept is 3.9%. This means that socioeconomic status can be used as a predictor to predict self-concept. Keywords: Correlation, socio-economic status, self concept..